PRACTICE OF IMPLEMENTING THE NATIONAL CLASSIFICATION OF OCCUPATIONS OF DEVELOPED COUNTRIES INTO THE LABOR MARKET (SAUDI ARABIA) (Multidisciplinary Journal of Science and Technology, 2026)
This article analyzes the practice of implementing a national classification of occupations into the labor market based on the experience of developed countries, using Saudi Arabia as a case study. The study examines the process of developing the Saudi Standard Classification of Occupations (SSCO), its regulatory and legal framework, and its alignment with international standards, particularly the International Standard Classification of Occupations (ISCO-08), the International Standard Classification of Education (ISCED-11), and the International Standard Classification of Education Fields (ISCED-13). In addition, the structure of the classification, its hierarchical framework based on skill and qualification levels, and its practical significance for the labor market, the education system, and human resource management are explored. The findings indicate that the Saudi Arabian experience demonstrates the importance of a systematic, scientific, and institutional approach to the development and effective implementation of a national classification of occupations in the labor market. Based on this model, recommendations for its application under the conditions of Uzbekistan are proposed.